A case of relapsing–remitting tumour-like inflammation of the central nervous system. (November 2015) - Miante, Silvia; Perini, Paola; Rinaldi, Francesca; Gallo, Paolo
The case of a 37-year-old woman suffering from a relapsing–remitting tumefactive inflammatory disease of the central nervous system (CNS) is described. The patient had four severe relapses over eight years, and was treated with steroids, immunosuppression and plasma-exchange with modest benefit. No magnetic resonance imaging or cerebrospinal spinal fluid findings suggestive of multiple sclerosis emerged during the eight-year follow-up. 'Relapsing–remitting tumefactive inflammation' seems to have the features of a distinct inflammatory CNS disease.